Sensible and latent heat loss from the body surface of Holstein cows in a tropical environment - Maia, ASC; daSilva, R. G.; Loureiro, CMB (Springer, 2005)
The general principles of the mechanisms of heat transfer are well known, but knowledge of the transition between evaporative and non-evaporative heat loss by Holstein cows in field conditions must be improved, especially for low-latitude environments. With this aim 15 Holstein cows managed in open pasture were observed in a tropical region. The latent heat loss from the body surface of the animals was measured by means of a ventilated capsule, while convective heat transfer was estimated by the theory of convection from a horizontal cylinder and by the long-wave radiation exchange based on the Stefan-Boltzmann law. When the air temperature was between 10 and 36 degrees C the sensible heat transfer varied from 160 to -30 W m(-2), while the latent heat loss by cutaneous evaporation increased from 30 to 350 W m(-2). Heat loss by cutaneous evaporation accounted for 20-30% of the total heat loss when air temperatures ranged from 10 to 20 degrees C. At air temperatures > 30 degrees C cutaneous evaporation becomes the main avenue of heat loss, accounting for approximately 85% of the total heat loss, while the rest is lost by respiratory evaporation.
Keywords: thermoregulation; Holstein cows; body surface; heat loss; tropical environment